2009
DOI: 10.1149/1.3062941
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanisms of Oxygen Surface Exchange on La[sub 0.6]Sr[sub 0.4]FeO[sub 3−δ] Thin Films

Abstract: The thermodynamic properties as well as oxygen exchange kinetics were examined on mixed ionic and electronic conducting ͑La 0.6 Sr 0.4 ͒ 0.99 FeO3 −␦ ͑LSF64͒ thin films deposited on MgO single crystals. It is found that thin films and bulk material have the same oxygen stoichiometry for a given temperature and oxygen partial pressure ͓i.e., the incorporation reaction has the same reaction enthalpy ͑⌬H 0 = −105 KJ/mol͒ and entropy ͑⌬S 0 = −75.5 J/mol/K͒ as found for bulk material͔. The thin film shows smaller a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
95
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 37 publications
2
95
1
Order By: Relevance
“…First, the ohmic component increased from 0.25 · cm 2 at p(O 2 ) = 1 atm to 0.39 · cm 2 at p(O 2 ) = 0.01 atm, implying that there was a decrease in the conductivity of the LSF-YSZ. 10,31 The increased ohmic resistance is observed here because the conductivity of LSF-YSZ electrodes prepared by infiltration are lower following calcination to 1373 K. 31 Second, there was a significant change in the shape of the non-ohmic part of the Nyquist plots with decreasing p(O 2 ). As noted above, there are at least two arcs in the spectrum for the 1373-K composite, corresponding to low (LF) and high (HF) frequency processes, with the LF feature gaining in prominence with decreasing p(O 2 ).…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…First, the ohmic component increased from 0.25 · cm 2 at p(O 2 ) = 1 atm to 0.39 · cm 2 at p(O 2 ) = 0.01 atm, implying that there was a decrease in the conductivity of the LSF-YSZ. 10,31 The increased ohmic resistance is observed here because the conductivity of LSF-YSZ electrodes prepared by infiltration are lower following calcination to 1373 K. 31 Second, there was a significant change in the shape of the non-ohmic part of the Nyquist plots with decreasing p(O 2 ). As noted above, there are at least two arcs in the spectrum for the 1373-K composite, corresponding to low (LF) and high (HF) frequency processes, with the LF feature gaining in prominence with decreasing p(O 2 ).…”
Section: Resultsmentioning
confidence: 69%
“…7,9,[16][17][18][19][20][21][22][23][24] Finally, a number of mathematical models have stressed the importance of maximizing the electrode active area 7,8,25,26 and point to the adsorption of molecular oxygen on a perovskite vacancy site as the most probable rate-limiting step. 7,8,10 Despite a large amount of work aimed at characterizing the oxygenreduction reaction on various materials, there is still much that is not known about the reaction or how to promote it. Characterization of oxygen reduction on working electrodes can be particularly difficult because high performance SOFC cathodes are usually composites of the conductive perovskite and the electrolyte material (e.g.…”
mentioning
confidence: 99%
“…[3][4][5] Therefore, generally other compositions such as (La,Sr)(Cr,Mn)O 3 , [6][7][8][9] (La,Sr)(Cr,V)O 3 , 10,11 (La,Sr)(Cr,Ru)O 3 , 12,13 or La and Fe doped SrTiO 3 14,15 are tested under reducing conditions. 16 Although Sr-doped LaFeO 3-δ (LSF) is a typical SOFC cathode material, it is also rather stable in reducing conditions, [17][18][19] with La 0.6 Sr 0.4 FeO 3-δ decomposing below 10 −27 bar pO 2 at 600…”
mentioning
confidence: 99%
“…For instance, chemical oxygen surface exchange coefficient (k) discrepancies greater than 4 orders of magnitude are reported at identical temperature and oxygen partial pressure conditions for the MIEC material La 0.6 Sr 0.4 FeO 3-δ (LSF64). [10][11][12][13] Similarly, large k discrepancies have been observed for other MIEC materials such as lanthanum strontium cobalt iron oxide [14][15][16][17] and reduced cerium oxide. [18][19][20][21] Since recent studies have shown that strain can alter k, 20,21 it is likely that some of these observed k discrepancies are due to differences in MIEC stress state.…”
mentioning
confidence: 87%